Effect of Variation of Adsorbent and pH Doses on Boron Adsorption Using DMAPAA-co-DMAPAAQ Hydrogel - Nugroho, Aldi; Aska, Silma Elvaretta; Venanto, Dimas Gilang; Ardiansyah, Erlangga; Taji, Lulu Sekar; Ningrum, Eva Oktavia (IPTEK The Journal of Engineering, 2024)
Boron is very dangerous for living things. The boron concentration allowed for drinking water is less than 1 mg/L. If not standard, boron causes nausea, lethargy, diarrhea, vomiting, dermatitis, and a risk of miscarriage in pregnant women. Thus, this research investigated the effect of variations in adsorbent dosage and pH on boron adsorption using the DMAPAA-co-DMAPAAQ hydrogel. The research began with the hydrogel synthesis process, which continued with the batch-mode sorption study. Based on research results, the higher the adsorbent dosage, the more boron is adsorbed. The highest removal percentage with an adsorbent amount of 0.5 g/L was 19.89% for pH 3, and for an adsorbent dosage of 2 g/L was 19.52% for pH 9. The highest percent removal was at pH 11. The DMAPAA-co-DMAPAAQ hydrogel adsorbent is shown to be environmentally friendly compared to commercial resins because the commercial resins are not biodegradable, making them difficult to recycle, causing more damage to the environment.